2020
DOI: 10.1097/bpo.0000000000001545
|View full text |Cite
|
Sign up to set email alerts
|

Can EOS Imaging Substitute for Conventional Radiography in Measurement of Acetabular Morphology in the Young Dysplastic Hip?

Abstract: Background: EOS imaging offers a low-radiation alternative to conventional radiography (CR) and has little to no magnification effects. However, it is unclear how radiographic measures may be affected using EOS. The present study aims to determine the reproducibility of measures of acetabular morphology on EOS images as compared with CR, and to directly compare the 2 imaging modalities. Methods: A total of 21 consecutive patients (66.7% female; 14.4±4.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…3) and increased risk of motion artifacts, especially in pediatric patients, due to a slow image acquisition process. 21 However, given that EOS appears to be equivalent to radiography for spine, hip, and chest imaging, 13,14 and putatively shunt This study has several limitations. It is retrospective and included only patients with shunted hydrocephalus due to Chiari type II malformations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…3) and increased risk of motion artifacts, especially in pediatric patients, due to a slow image acquisition process. 21 However, given that EOS appears to be equivalent to radiography for spine, hip, and chest imaging, 13,14 and putatively shunt This study has several limitations. It is retrospective and included only patients with shunted hydrocephalus due to Chiari type II malformations.…”
Section: Discussionmentioning
confidence: 92%
“…Orthopedic studies have compared EOS scans to conventional radiographs and found noninferior radiographs without distortions when analyzing spinal and pelvic angles and measurements. 13,14 A study by Hey et al compared full-body EOS images to conventional chest radiographic images for preoperative evaluation of patients undergoing spine surgery and found no significant differences between the two imaging modalities. 13 EOS has also proven equivalent to conventional radiography in the evaluation of preoperative spinal flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…While an interrater reliability analysis was not conducted, previously reported ICC for all measures included have been shown to be excellent. 23 This study includes patients from multiple sites and represents an international cohort of early-stage LCPD patients which improves its generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 All measurements were performed by 3 authors specifically for the purpose of this study (C.M.S., J.T.B., and W.N.S.). Intrarater and interrater reliability has been previously measured in multiple studies, and intraclass correlation coefficients (ICC) values have been well-established for the following metrics: EI (0.80 to 0.96); LCEA (0.64 to 0.97); AI/Tönnis (0.42 to 0.95) 23. Given these well-established ICC values, each observer measured one-third of the radiographs included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Although three dimensional structure of hip joint can be derived from CT and MRI images, it has to be faced with relatively high fees of medical check and high radiation. Therefore, the radiograph of pelvis from a X-ray film becomes the main early diagnosis of hip dysplasia (Kayaalp et al, 2020;Powell et al, 2020). Inevitably, the ever-growing numbers of X-ray films increase the burden of radiologists.…”
Section: Introductionmentioning
confidence: 99%